Sugarcane Variety Census: Florida 2003 - B. Glaz; J. Vonderwell; Robert A. Gilbert (EDIS)
This document is SS AGR 266, part of the Florida Sugarcane Handbook, published by the UF Agronomy Department, June - October 2007.